2007
DOI: 10.1007/s11064-007-9331-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased Membrane/Nuclear Translocation and Phosphorylation of p90 KD Ribosomal S6 Kinase in the Brain of Hypoxic Preconditioned Mice

Abstract: Our previous studies have demonstrated that hypoxic precondition (HPC) increased membrane translocation of protein kinase C isoforms and decreased phosphorylation of extracellular signal-regulated kinase 1/2 (ERK1/2) in the brain of mice. The goal of this study was to determine the involvement of p90 KD ribosomal S6 kinase (RSK) in cerebral HPC of mice. Using Western-blot analysis, we found that the levels of membrane/nuclear translocation, but not protein expression of RSK increased significantly in the front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Ischemic/hypoxic preconditioning is a hypoxia-induced endogenous tolerance to protect cells from injuries caused by subsequent severe hypoxia injury. This phenomenon of protection had been widely observed in many organs and tissues, such as heart and brain [18,19]. Zhang et al employed the ischemic preconditioning model of microvascular endothelial cells (HBMECs) as the vitro model to demonstrate that hypoxic preconditioning inhibited endothelial cells death from apoptotic through the phosphatidylinositol 3-kinase (PI3-kinase)/Akt pathway [20].…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic/hypoxic preconditioning is a hypoxia-induced endogenous tolerance to protect cells from injuries caused by subsequent severe hypoxia injury. This phenomenon of protection had been widely observed in many organs and tissues, such as heart and brain [18,19]. Zhang et al employed the ischemic preconditioning model of microvascular endothelial cells (HBMECs) as the vitro model to demonstrate that hypoxic preconditioning inhibited endothelial cells death from apoptotic through the phosphatidylinositol 3-kinase (PI3-kinase)/Akt pathway [20].…”
Section: Discussionmentioning
confidence: 99%
“…RSK2 is as well implicated in cellular functions (10,11,15,23,36,52) and tumorigenesis (12,33). Although RSK is known to be regulated at the posttranscriptional level by phosphorylation (12,36), it has also been shown that the expression of RSK protein in the frontal cortex is enhanced by hypoxic preconditioning (44) or traumatic stress (54). In this work, we found that daily stress exposure induced dorsal horn RSK2 expression in the dorsal horn of rats.…”
Section: Discussionmentioning
confidence: 56%
“…It's a suitable ischemic-hypoxic preconditioning model that could be observed clinically. Using this model, we have observed that protein kinase C (PKC) isoforms and its substrate neurogranin (Ng) [18,24,26], cAMP response element binding protein (CREB) [19], ERK1/2 [27], p38 MAPK [22], JNK/SAPK [21], mitogenand stress-activated protein kinase-1 (MSK-1) [20], and p90 KD ribosomal S6 kinase (RSK) [23] were involved in the development of cerebral HPC of mice.…”
Section: Discussionmentioning
confidence: 99%
“…and perfused transcardially with 0.9% NaCl followed by 4% paraformaldehyde as our previous reports [22,23]. The brains were removed quickly, post-fixed for 24 h in 4% paraformaldehyde and dehydrated in 20% sucrose solution.…”
Section: Immunostaining Studymentioning
confidence: 99%